Identification of cell-free microRNAs in the urine of patients with prostate cancer - Korzeniewski, Nina; Tosev, Georgi; Pahernik, Sascha; Hadaschik, Boris; Hohenfellner, Markus; Duensing, Stefan (Urologic oncology, 2015)
Current methods for the early detection of prostate cancer (PCa), in particular prostate-specific antigen screening, are likely to benefit from complementary molecular analyses to enhance specificity. MicroRNAs (miRNA) are small endogenously expressed noncoding RNAs that negatively regulate the expression of protein-coding genes at the transcriptional or translational level. Accumulating evidence suggests that miRNAs play an important role in tumorigenesis, are differentially expressed in different cancer types, and can be found in all bodily fluids so-far tested, including urine.